Predictors and potential risk factors of iatrogenic ureteral injury following common obstetric and gynecological surgeries: A single-center retrospective study - Yahya Ghazwani; Nasser Albogami; Mohammed Aldwaighri; Ghassan Alhajress; Abdullah Alsaghyir; Faisal Balaraj (Urology Annals)
Objectives: As iatrogenic ureteral injury carries a high burden and is associated with increased postoperative morbidity and mortality, the purpose of this study is to determine the incidence and potential risk factors of iatrogenic ureteral injury following common obstetric and gynecological surgeries in King Abdulaziz Medical City. Methods: This was a single-center retrospective cohort study based on data extracted from an electronic hospital information system conducted in King Abdulaziz Medical City, Riyadh, Saudi Arabia. Three thousand four hundred and sixty-four cases of cesarean section (C-section) and hysterectomy from January 1, 2021, to December 31, 2022, were reviewed. All cases of C-section and hysterectomy in which the urology department was consulted for suspected iatrogenic ureteric injuries were included in the study. All cases other than C-sections and hysterectomy in which the urology department was consulted for suspected iatrogenic ureteric injuries were excluded from the study. Results: A total of 45 patients for whom urology was consulted for suspected ureteral injury were included in this study. Approximately (35.6%) one-third of the patients had positive findings of ureteral injury following common obstetric and gynecological surgeries. About 41.2% of these patients had previous gynecological surgeries. Other potential risk factors were tested such as age and body mass index. Older patients were slightly at higher risk of iatrogenic ureteral injury (P < 0.05). Conclusion: Ureteral injury in obstetric and gynecological surgeries is rare yet serious complication. The findings of this study suggest that the incidence of iatrogenic ureteral injury was relatively associated with older age.